Hysterolaparoscopy as a one-time approach in infertility: a prospective study - Sutaria, Rini; Singh, Richa; Gopal, Sriram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The prevalence of infertility ranges from 3.5% to 16.7% in more developed nations and from 6.9% to 9.3% in less developed nations, with an estimated overall median prevalence of 9%. The present study was aimed to evaluate the role of hysterolaparoscopy in the study of primary and secondary infertility, to identify the various pathological conditions in female reproductive tract leading to primary/ secondary infertility, to develop a plan for therapy and management at the same time. Methods: This is a one-year prospective study conducted in obstetrics and gynecology department at D. Y. Patil hospital, Navi Mumbai, Maharashtra, India. All infertility patients seen in outpatient department, who were medically fit, willing for surgery and willing to get enrolled for study were included in this study. Results: Out of total 120 cases for infertility evaluated, tubal factor is the most common cause (28.3%) in both primary (23.3%) and secondary (43.3%) infertility group as seen on laparoscopy. Followed by ovarian factors (28.3%), peritoneal (11.6%) and uterine factors (10.8%). In 27 cases (22%), there were no detectable pathology at laparoscopy. In this study, hysteroscopy findings show 5.8% cases to have submucous fibroid uterus, 3.3% submucous polyp, 1.6% subseptate uterus, 0.8% septate uterus, 0.8% intrauterine adhesions, 0.8% bicornuate uterus and cervical stenosis 1.6% of patients. Conclusions: From this study, it is concluded that the diagnostic hysteroscopy and laparoscopy is an effective and safe tool in evaluation of female infertility. It provides direct and magnified view of all pelvic organs.